2017
DOI: 10.31018/jans.v9i2.1277
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of mixed fruit cheese from Guava (Psidiumguajava cv. Hisar Safeda) and Mango (Mangiferaindica var. Safeda) and its quality evaluation during storage

Abstract: The present investigation was carried out to prepare fruit cheese, a fruit confectionery prepared by combining fruit pulp with sugar, pectin and acid from blended fruit pulp of guava (Psidiumguajava) and mango (Mangiferaindica). The storage studies of mixed fruit cheese packed in HDPE bags showed significant changes in chemical properties during three months storage. Total sugars, reducing sugars and browning increased significantly from 66.8 to 68.7 %, 21.1 to 23.4 % and 0.25 to 0.37, while carotenoids and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Similar findings were reported by Sucheta et al (2017) during storage in guava-mango cheese storage for 90 days where browning increased from 0.25 to 0.37 during storage of 90 days. Kumar et al (2019b) found similar increase in browning of aonla-papaya cheese with storage.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Similar findings were reported by Sucheta et al (2017) during storage in guava-mango cheese storage for 90 days where browning increased from 0.25 to 0.37 during storage of 90 days. Kumar et al (2019b) found similar increase in browning of aonla-papaya cheese with storage.…”
Section: Resultssupporting
confidence: 88%
“…Fruit cheese is a chewable confectionary product which is relatively new to fruit processors. Fruits like pineapple, apple, papaya, banana, pear and plum have been used for preparing fruit cheese yet there are many fruits like jamun and bael which are unexploited by the food processing industries (Sucheta et al, 2017). Jamun (Syzygium cumini L.) belongs to Myrtaceae family.…”
Section: Introductionmentioning
confidence: 99%
“…Author(s) agree that this article remain permanently open access under the terms of the Creative Commons Attribution License 4.0 International License studies that investigated the nutrient content of guava together with one other fruit such as orange (Srivastava et al, 2019), papaya (Bisen and Ruchi, 2020) and mango (Sucheta et al, 2017). Products made from the ripe jackfruit already investigated are jackfruit powder (Ahiduzzaman, 2016), jackfruit chips (Yi et al, 2016), jelly, syrup and jams (Mondal, 2013).…”
Section: Introductionmentioning
confidence: 99%